PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM: TINJAUAN KEPUSTAKAAN TENTANG PENDEKATAN, MODEL, DAN TANTANGAN KONTEKSTUAL - Suniati; Nanang Budianto; Nur Rofi’ah; Maksum (PT. Hasba Edukasi Mandiri, 2026)
The curriculum of Islamic Religious Education (Pendidikan Agama Islam/PAI) holds a strategic position within the national education system, as it functions to instill faith, morality, and social piety in learners. Nevertheless, the PAI curriculum at various educational levels is frequently regarded as overly normative-cognitive, insufficiently contextual to social, cultural, and technological change, and not yet fully responsive to twenty-first-century competency demands. This study aims to describe the basic concepts, approaches, models, and supporting and inhibiting factors in the development of the PAI curriculum, while also examining the relevance of interdisciplinary and multidisciplinary approaches as an alternative direction for renewal. This study employs a qualitative method in the form of library research. Data were collected from books, accredited journal articles, and relevant prior studies, then analyzed descriptively and analytically through the stages of data reduction, data display, and conclusion drawing. The findings indicate that PAI curriculum development can be pursued through both technical and non-technical approaches, with models ranging from the subject-centered model and the competency-based model to the thematic-integrative model. Supporting factors include government policy, teacher readiness, and facility support, while inhibiting factors include limited resources, resistance to change, and weak integration across subjects. This study recommends that future development of the PAI curriculum move toward an integrative model that combines Islamic values with science, technology, and character strengthening through an interdisciplinary approach.